Assessment of 12 qualitative RT‐PCR commercial kits for the detection of SARS‐CoV‐2 - Altamimi, Asmaa M. (J Med Virol, 2021)
The emergence of the novel coronavirus, the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) in the late months of 2019 had the officials to declare a public health emergency leading to a global response. Public measurements rely on an accurate diagnosis of individuals infected with the virus by using real‐time reverse transcriptase‐polymerase chain reaction (RT‐PCR). The aim of our study is to relate the fundamental clinical and analytical performance of SARS‐CoV‐2 (RT‐PCR) commercial kits. A total of 94 clinical samples were selected. Generally, 400  µl of each respiratory specimen was subjected to extraction using ExiPrep 96 Viral RNA Kit. All kits master mix preparation, cycling protocol, thermocycler, and results interpretation were carried out according to the manufacturer's instructions of use and recommendations. The performance of the kits was comparable except for the LYRA kit as it was less sensitive (F = 67, p < .001). Overall, four kits scored a sensitivity of 100% including: BGI, IQ Real, Sansure, and RADI. For specificity, all the tested kits scored above 95%. The performance of these commercial kits by gene target showed no significant change in CT values which indicates that kits disparities are mainly linked to the oligonucleotide of the gene target. We believe that most of the commercially available RT‐PCR kits included in this study can be used for routine diagnosis of patients with SARS‐CoV‐2. We recommend including kits with multiple targets in order to monitor the virus changes over time.